Analysis of thermal stability of the internal structure of Ag-Cu nanoparticles - A.A. Cherepovskaya; S.L. Gafner; Yu.Ya. Gafner; D.A. Ryzhkova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
Binary nanoparticles of the copper-silver alloy of are of great practical interest due to the possibility of fine-tuning their physical and chemical properties by changing the composition, size, shape and structure of nanoparticles. The processes of formation of the internal structure of Ag-Cu nanoparticles with a diameter from 2.0 to 8.0 nm during their crystallization with three different rates of thermal energy dissipation were studied by the molecular dynamics method. The features of this process were found to be dependent on the target chemical composition of nanoparticles, their size and the intensity of the thermal energy dissipation. The actual appearance and structure of the studied nanoparticles were determined using OVITO and xmakemol visualizers. It was shown that as a result of crystallization from the melt of binary Ag-Cu nanoparticles, metastable states that are sufficiently stable at room temperature (300 K), and the stability of such states after annealing at a temperature of 600 K is also evaluated.